Faktor-Faktor yang Berhubungan dengan Kelelahan dalam Pembelajaran Online pada Mahasiswa STIKes PHI - Ririn Nobrianti; Elwindra Elwindra (Jurnal Persada Husada Indonesia, 2023)
The SARS-CoV-2 virus (Covid-19) was first detected in China in late 2019 and has spread worldwide by June 2021. The social distancing measures implemented by the Indonesian government have impacted teaching and learning activities. As a result, students have had to engage in online learning using devices such as smartphones, computers, or laptops for the duration of their lectures. The emission of light from these electronic devices can cause both physical and mental fatigue. This study aims to identify the factors related to fatigue in online learning among students at STIKes PHI in 2022. This research is quantitative in nature and adopts an analytical survey method using a cross-sectional approach. The population of this study consists of all STIKes PHI students, totalling 123 students, with a sample size of 94 students selected using stratified random sampling. The results of the study show that 70 (74.5%) students experience moderate levels of fatigue. From the bivariate analysis, two factors were found to be related to fatigue in online learning, which are duration (P-value 0.009) and study time (P-value 0.007). It was found that as the duration of online learning increases (> 3 hours) and the study, time is in the afternoon, students experience higher levels of fatigue. It is recommended that the campus management distribute the duration of online learning more evenly to avoid excessively long sessions and prioritize morning study times.